High Protein- and High Lipid-Producing Microalgae from Northern Australia as Potential Feedstock for Animal Feed and Biodiesel - Duong, Van Thang; Ahmed, Faruq; Thomas-Hall, Skye R.; Quigley, Simon; Nowak, Ekaterina; Schenk, Peer M. (Frontiers in Bioengineering and Biotechnology, 2015)
Microalgal biomass can be used for biodiesel, feed and food production. Collection and identification of local microalgal strains in the Northern Territory – Australia was conducted to identify strains with high protein and lipid contents as potential feedstock for animal feed and biodiesel production, respectively. A total of 36 strains were isolated from 13 samples collected from a variety of freshwater locations, such as dams, ponds and streams and subsequently classified by 18S rDNA sequencing. All of the strains were green microalgae and predominantly belong to Chlorella sp., Scenedesmus sp., Desmodesmus sp., Chlamydomonas sp., Pseudomuriella sp., Tetraedron caudatum, Graesiella emersonii and Mychonastes timauensis. Among the fastest growing strains, Scenedesmus sp. NT1d possessed the highest content of protein; reaching up to 33% of its dry weight. In terms of lipid production, Chlorella sp. NT8a and Scenedesmus dimorphus NT8e produced the highest triglyceride contents of 116.9 µg mL-1 culture and 99.13 µg mL-1, respectively, as measured by gas chromatography-mass spectroscopy (GC-MS) of fatty acid methyl esters (FAMEs). These strains may present suitable candidates for biodiesel production after further optimization of culturing conditions, while their protein-rich biomass could be used for animal feed.